Efficacy of alcohol screening in the accident and emergency department managed by reception staff: a pilot study. Issue 6 (22nd May 2009) - Patton, R; Shute, J; Hinchley, G; Ranzetta, L
Abstract : Hazardous levels of alcohol consumption are associated with presentations to the accident and emergency department. Although screening and brief interventions are effective at reducing levels of hazardous drinking, a low number of departments has implemented such a strategy. Time constraints upon clinical staff have been cited as one reason for this inertia. This pilot study demonstrates that self-completion of screening materials is possible before a patient is seen by clinical staff.